The way of a Sufi, Sharafuddin Maneri - Jackson, Paul, 1937- (Delhi : Idarah-i Adabiyat-i Delli, 1987)
Life and teachings of Sharaf al-Din Ahmad ibn Yahya, d. 1380?, Sufi saint from Bihar.
Includes index.
Bibliography: p. [251]-255.
Keywords: Maniri, Sharaf al-Din Ahmad ibn Yahya, -- -1380?.; Sufis -- India -- Bihar -- Biography